Metabolomic Analysis of the Effects of Adipose-Derived Mesenchymal Stem Cell Treatment on Rats With Sepsis-Induced Acute Lung Injury - Cui, Yuqing; Liu, Shaohua; Zhang, Xiaojuan; Ding, Xianfei; Duan, Xiaoguang; Zhu, Zijia; Zhang, Ji; Liang, Huoyan; Wang, Dong; Zhang, Guojun; Yu, Zujiang; Yang, Jianjun; et al. (Frontiers in Pharmacology, 2020)
Given the high mortality associated with sepsis, there is an urgent need for a full understanding of sepsis pathophysiology and finding new therapeutic regimens. Adipose-derived mesenchymal stem cells (ADMSCs) has been proven to have anti-inflammatory effects and could be used to treat cecal ligation and puncture (CLP) induced lung and liver injury in septic rat models. In this study, we used metabolomics to investigate small molecule metabolites between CLP and ADMSCs treatment groups. Sixty SD rats were randomly assigned to the sham operation group (SC group), the CLP group, and the CLP+ADMSCs group (CLP-ADMSCs group). We used liquid mass spectrometry-chromatography to detect metabolic changes in plasma and lung tissues. Compared with the SC group, the metabolic profile of plasma and lung tissues changed significantly 24 h after CLP. Moreover, 22 and 11 main differential metabolites involved in amino acid and glycerophospholipid metabolism were found in plasma and lung tissues, respectively. After the rats were injected with ADMSCs, these differential metabolites were reverse-regulated both in plasma and lung tissues. Besides, ADMSCs improved the survival rate and down-regulated the concentration of TNF-α and IL-6 at 24 h after CLP. The correlational analysis between plasma of IL-6/TNF-α and metabolites suggested that acetylcholine, spermine, phenylalanine, threonine of plasma and phosphatidylcholine (36:4) of lung tissues were significantly associated with IL-6/TNF-α in CLP and CLP-ADMSCs groups. ADMSCs might reverse abnormal metabolic pathways by reducing anti-inflammatory factors in sepsis-induced ALI. Our findings may provide novel metabolic mechanism of ADMSCs therapy for sepsis.